Analysis of the USDA’s 2017 Cow-Calf Management Practices Results: Part 3—Natural Service and Bull Management - João Bittar; Mario Binelli; Angela Maria Gonella-Diaza (EDIS)
This article aims to present and discuss the most common management practices related to bull use that can impact cow-calf production and to share relevant statistics of bull use based on the last USDA surveys. Written by João Bittar, Mario Binelli, and Angela Gonella, and published by the UF/IFAS Department of Animal Sciences, September 2022.